2017
DOI: 10.1177/1367493517738124
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric testing of the Turkish version of the Health Literacy for School-Aged Children Scale

Abstract: This study aimed to assess the validity and reliability of the Turkish version of the Health Literacy for School-Aged Children (HLSAC-T) scale. This study was a cross-sectional and methodological design. The sample consisted of 563 sixth and ninth grade students in Izmir, Turkey. Data were collected with the socio-demographic characteristics questionnaire, HLSAC-T, and Turkish version of the Adolescent Lifestyle Profile. Cronbach's α for the scale was .77 and item-total correlations were between .49 and .61 ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 27 publications
(33 reference statements)
2
37
0
1
Order By: Relevance
“…The factor loads ranged between 0.30 and 0.55. These results indicate that the scale is a valid and reliable tool for Turkish studies (Haney, 2018).…”
Section: Health Literacy Scale For School-aged Childrenmentioning
confidence: 55%
See 1 more Smart Citation
“…The factor loads ranged between 0.30 and 0.55. These results indicate that the scale is a valid and reliable tool for Turkish studies (Haney, 2018).…”
Section: Health Literacy Scale For School-aged Childrenmentioning
confidence: 55%
“…The alpha value of the original scale was 0.93, and the alpha values of the subscales ranged from 0.69 to 0.77 (Paakkari et al, 2016). The validity and reliability of the Turkish version of the scale were examined by Haney (2018). The Cronbach's alpha coefficient was 0.77; the Turkish version of the scale had an RMSEA value below 0.08, and the fit indices were above 0.90.…”
Section: Health Literacy Scale For School-aged Childrenmentioning
confidence: 99%
“…Six selected studies were recently published, from 2016 to 2019. The studies were conducted in several countries such as Iran, Turkey, Finland, China, Lithuania [13][14][15][16][17][18] . Characteristics of the study is shown in Table 1.…”
Section: Descriptive Characteristics Of the Studiesmentioning
confidence: 99%
“…The respondents in the studies ranged from 11 to 18 years, and most were students of various selected schools. In general, the studies aimed to develop and evaluate the instrument related to health literacy in children 14,16,17 . Other studies compared health literacy in children who engaged in certain physical activities such as sports 15 .…”
Section: Descriptive Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation